Overview of factors affecting work life balance in student part-time workers - Hidayatullah, Teguh; Prihastuty, Rahmawati (Universitas Negeri Semarang, 2023)
It is very important to balance between work and life outside of work for students who continue to study while working. The phenomenon of students studying while working can find at Semarang State University. Students who work and study must maintain a work-life balance. The purpose of this research is to identify the factors that influence the work-life balance of part-time students at Semarang State University. The research method used was qualitative research with descriptive narrative approaching. This study's data comes from interviews and observations of the subject, namely active students in semesters 1-6 who work part-time on a total of three subjects. Perspective triangulation, time triangulation, and method triangulation were used in conjunction. Data analysis techniques, such as data collection, data transcription, data presentation, and conclusions. The study’s finding indicate that there are three factors influence the work life balance of part-time student workers, they are internal and external work conditions, also individual internal conditions. The findings of this study will enable us to add references about the factors that influence the work-life balance and provide information for students who want to attend college while working a part-time job.